Pengaruh Lama Penjemuran dan Lama Pembakaran terhadap Perkecambahan Benih Kemiri (Aleurites moluccana) - Patrick Gaudens Pirikus; Astin E. Mau; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
This study aimed to evaluate the effects of physical scarification methods-specifically sun drying and burning treatments-on candlenut seed germination. A Completely Randomized Design (CRD) with two factors, duration of sun drying and duration of burning, was implemented. The sun drying treatments included: A0 = control (no drying), A1 = 24 hours, A2 = 20 hours, and A3 = 16 hours. The burning treatments comprised: B0 = control (no burning), B1 = 5 minutes, and B2 = 10 minutes. Each treatment was replicated three times for a total of 36 experimental units, with 10 seeds per unit (360 seeds total). Data were analyzed by Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the individual treatments A2 (20 hours of sun drying) and B1 (5 minutes of burning) significantly enhanced germination percentage, germination rate, number of leaves, and seedling height. An interaction effect between sun drying and burning was statistically significant for germination rate and seedling height but not for germination percentage or number of leaves.